Diagnostic systems of electric motors in real time - Кучерук, В.Ю.; Войтович, О.П. (Proceedings of National Aviation University, 2007)
Thesis is devoted to development and research of system of electromotor diagnosis, which is working on increasing angular velocity. The methods of electromotor diagnosis with complexly taking into account faults by special testing and continuous inspection based on neural-fuzzy methods are developed. Based on offered methods formed hardware and software, which are used in developed system of electromotor diagnosis. The analog neuralcontroller using is offered. The main preferences of such approach are accuracy and speed of diagnoses receiving due to data processing with analog measurement channel.